2015
DOI: 10.1111/sode.12135
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Young Children's Socially Adaptive Resolutions of Peer Conflict

Abstract: How do young children negotiate conflicts with peers that result in mutually beneficial resolution and peaceful interaction after conflict? A few studies suggest that when children use conciliatory strategies in conflict, socially adaptive outcomes are more likely to be achieved. The present study explores the relative associations of types of children's conciliatory conflict resolution strategies (i.e., prosocial, compliance‐oriented, solution‐oriented, and verbal clarification/apology) with conflict outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…conflicts via negotiation, Spivak, 2016). Contrary to the positive association between separating behavioral problems and peer liking documented in Gest and Rodkin's study with first, third, and fifth grade students, separating behavioral problems did not predict changes in children's friendships or peer conflicts in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…conflicts via negotiation, Spivak, 2016). Contrary to the positive association between separating behavioral problems and peer liking documented in Gest and Rodkin's study with first, third, and fifth grade students, separating behavioral problems did not predict changes in children's friendships or peer conflicts in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with Gest and Rodkin’s (2011) findings, teachers in this study reported viewing strategies for separating students with behavior problems as more important than ability grouping or strategies for forming existing or new friendships strategies when they create seating charts or form small groups. This finding is also aligned with the conflict intervention literature showing that early childhood teachers tend to intervene in peer conflicts mainly when the conflicts escalate (Myrtil et al, unpublished); when the teachers intervene, they tend to use more cessation strategies (e.g., directly separating conflict peers) than mediation strategies (e.g., guiding students to resolve conflicts via negotiation, Spivak, 2016 ). Contrary to the positive association between separating behavioral problems and peer liking documented in Gest and Rodkin’s study with first, third, and fifth grade students, separating behavioral problems did not predict changes in children’s friendships or peer conflicts in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, while we grant that cooperation plays a fundamental role in moral development, young children also disagree with parents, peers, and siblings about which clothes they should wear, who owns which toy, and whether it is okay to hit back (Dahl 2014;Nucci & Weber 1995;Ross et al 2014;Smetana et al 2012;Wainryb et al 2005). The dynamics of young children's resolutions to peer conflict reveal that prosocial behaviors during conflict are related to peaceful post-conflict interactions, indicating that cooperation often stems from interpersonal conflict (Spivak 2016).…”
Section: The Moral Obligations Of Conflict and Resistancementioning
confidence: 99%
“…Thus, while we grant that cooperation plays a fundamental role in moral development, young children also disagree with parents, peers, and siblings about which clothes they should wear, who owns which toy, and whether it is okay to hit back (Dahl 2014; Nucci & Weber 1995; Ross et al 2014; Smetana et al 2012; Wainryb et al 2005). The dynamics of young children's resolutions to peer conflict reveal that prosocial behaviors during conflict are related to peaceful post-conflict interactions, indicating that cooperation often stems from interpersonal conflict (Spivak 2016).…”
mentioning
confidence: 99%